Proceedings of the 2007 InSITE Conference 2007
DOI: 10.28945/3086
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Warranty and the Risk of Information Asymmetry

Abstract: Nowadays the product warranty is considered to be a valuable attribute of the product. It is a tool to enforce the competing power of the producer on the market place. There are two types of problems the product warranty addresses. Firstly, warranty deals with the malfunctioning of the product and, secondly, it addresses the information asymmetry, i.e., the misunderstanding and misinterpretation of the features and qualities of the product. The second aspect is of great importance in the light of indirect busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
(3 reference statements)
1
14
0
Order By: Relevance
“…If the impact of information asymmetry is disregarded, the risk of being misinformed is underestimated and often ignored in purchase decision making. In data collected in an empirical study, published in Christozov, Chukova, and Mateev (2007) among 65 respondents only 6 recognized their uncertainty of whether the product is suitable for their needs. The data revealed that the overall risk of making a wrong decision was above 40%.…”
Section: The Role Of Warranty Of Misinforming In the Productmentioning
confidence: 99%
“…If the impact of information asymmetry is disregarded, the risk of being misinformed is underestimated and often ignored in purchase decision making. In data collected in an empirical study, published in Christozov, Chukova, and Mateev (2007) among 65 respondents only 6 recognized their uncertainty of whether the product is suitable for their needs. The data revealed that the overall risk of making a wrong decision was above 40%.…”
Section: The Role Of Warranty Of Misinforming In the Productmentioning
confidence: 99%
“…Next, we extend the model for quantifying the risk of misinforming, proposed in Christozov, Chukova, and Mateev (2007) study. One of the main difficulties in quantifying the risk of misinforming is that the risk is subjective, i.e., one and the same message containing information on the product of interest, may convey correct information to some customers and misinform others.…”
Section: Quantitative Measure Of the Risk Of Misinformingmentioning
confidence: 99%
“…describes the set of tasks as a union of buyers' tasks, whereas A * is the same set of tasks from task category point of view, (for details, see Christozov, Chukova, and Mateev (2007)). For completeness, we assume that all buyers need to solve for all tasks, but for some of these tasks the buyer's need to solve is equal to zero.…”
Section: Description Of the Tasks (Problems)mentioning
confidence: 99%
See 2 more Smart Citations